The Effect of PlantNet Application on Students' Learning Outcomes in Plant Classification: A Quasi-Experimental Study - khairiati umami; Jalaluddin Jalaluddin; Anita Noviyanti; Jailani Jailani; Fakhrurrazi Fakhrurrazi (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
This research aims to address the low understanding of students in the material of plant classification which is caused by the learning activity that is primarily theoretical and lacks a direct learning experience. This study aims to analyse the effectiveness of the PlantNet application in improving the learning outcomes of tenth-grade students at MAN 1 Banda Aceh. This is quantitative research with quasi experimental method with the design of one group pretest-posttest design, and the number of samples are 40 students, taken by simple random sampling. The data collection instruments were observation sheets, pretest and posttest instruments and student response questionnaires. The results showed an increase in students’ learning outcomes with an average score of 82.3 to 98.1 and an N-Gain score of 0.89 in the high category. The mean difference test showed a statistically significant difference in students’ learning outcomes before and after the implementation of the PlantNet application. In addition, the student responses to the use of the application are very good. Results of this study show that the application of PlantNet is effective in improving student learning results on plant classification material and provides meaningful learning supported by technology.